STRATEGY FOR IMPROVING PURCHASING POWER OF PEOPLE THROUGH SCIENCE AND TECHNOLOGY FOR THE FARMERS ROSELA - Diah, Mardiah (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2015)
The increase in revenues is one way to increase purchasing power.  This community activities aimed   to increase the income of farmers  through  improving the knowledge of farmers. This can be done by improving  knowledge about the quality of the product, packaging of product, management of  bookkeeping, and marketing . Evaluation of these activities be done by monitoring all activities of product producing and  marketing  and seek information about the problem that happened as long as periode this activities.